Effects of Co Addition on the Microstructure and Morphological Properties of TIO2: Multicomponent Oxide of Transition Metals (2020)
This work presents the process of fabrication and characterization of cobalt-doped titanium dioxide thin films on soda-lime glass substrates useful in spintronic applications. The samples were fabricated via the DC Sputtering technique, under the magnetron configuration. The samples were submitted of annealing at atmospheric pressure, after deposit process. Annealing process affect the structural properties of thin films, evidencing the formation of the Co3O4 with spinel structure. XPS measurements corroborated the presence of cobalt oxide species with a spinel-like arrangement. Morphological characterization showed an overall granular nature of the fabricated samples, which varied depending on the deposition time and annealing process. PPMS measurements revealed a ferromagnetic behavior of the thin films at room temperature.